Maps as Collaborative Learning Media for Social Studies Learning on Imperialism and Colonialism in Indonesia - Suswandari; Qodariah, Lelly; Rahmawati, Melinda; Azid, Nurulwahida (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
This study seeks to see the usefulness of maps in social studies learning in visualizing the distribution of locations in the spice trade route. Maps can present information on the distribution of historical areas. This study aims to analyze and describe the usefulness of using maps as social studies learning media on spice trade materials in the archipelago. This study uses a qualitative method-case study of the presentation of spice trade materials in the archipelago in six Jakarta, Bogor, and Depok schools. This research confirms that using maps as a collaborative social studies learning medium is an effort to optimize the presentation of information related to the spice trade in the archipelago geographically and historically. This study concludes that maps are one of the collaborative learning media on spice trade materials in the archipelago in social studies learning.